Reusability of metallurgical slag waste in submerged arc welding powder for hardfacing - Kaptanoglu, Mustafa; Eroglu, Mehmet (Carl Hanser Verlag, 2020)
Slag waste generated during the metallurgical process in a ferrochromium plant in Elazig, Turkey, ferro alloys and other required ceramic based powders were mixed to obtain recycled powders produced by submerged arc welding using the agglomeration method. High carbon ferrochromium was also added to the recycled powder mixtures to improve the microstructure, hardness, and wear properties of SAE 1020 steel using a submerged arc welding technique for hardfacing. After the powder production and welding process, there were no crack and porosities on the surface of the hardfacings. As the amount of high carbon ferrochromium in the recycled powders increased, homogeneity and slag removal properties of the hardfacings decreased. Their microstructures changed, macrohardness values increased, and wear losses decreased. The highest macrohardness value 46 HRC and the lowest wear loss 4.8 g were observed in hardfacing obtained using the recycled powder with 16 wt.-% high carbon ferrochromium.
Keywords: Submerged arc welding; slag waste; hardfacing; recycling; ferrochromium